Atorvastatin ameliorates LPS‐induced inflammatory response by autophagy via AKT/mTOR signaling pathway. Issue 2 (7th September 2017) - Han, Fei; Xiao, Qing‐Qing; Peng, Shi; Che, Xin‐Yu; Jiang, Li‐Sheng; Shao, Qin; He, Ben
Abstract: Macrophages play crucial roles in immune response and atherosclerosis‐related cardiovascular disease. Recent evidence of macrophage autophagy has demonstrated a novel pathway through which contributes to vascular inflammation. The aim of this study was to elucidate the role of autophagy in the inhibition of inflammatory response in macrophages by atorvastatin. We found that atorvastatin promoted autophagy flow determined by up‐regulating the expression of autophagy‐related protein microtubule‐associated protein light chain (LC3B), inducing the formation of autophagosomes and down‐regulating the expression of SQSTM1/P62, which is consumed during autophagy. Atorvastatin also inhibited the expression of inflammatory factors IL‐1β and TNFα induced by LPS in RAW264.7 cells. Furthermore, pretreatment with an autophagy inhibitor 3MA or LY294002 attenuated the suppressive effect of atorvastatin on LPS‐induced IL‐1β and TNFα expression. Additionally, knockdown autophagy‐related gene 5(Atg5) with a special siRNA also prevented the role of atorvastatin in decreasing IL‐1β and TNFα release induced by LPS. Finally, we detected that AKT/mTOR/P70S6K signaling pathway was involved in atorvastatin‐induced autophagy in macrophages. These data suggest that atorvastatin attenuates LPS‐induced inflammatory factors secretion, at least in part, through enhancing autophagy by AKT/mTOR signaling pathway. Our findings provide a novel evidence that statins exert anti‐inflammatory effect in atherosclerosis by autophagy activation. Abstract : Atorvastatin exerted no effect on downregulation of IL‐1β and TNF‐α secretion by inhibition of autophagy either through knockdown of Atg5, or by treatment with the autophagy inhibitor 3‐MA or LY294002. Therefore, atorvastatin may activate autophagy to attenuate LPS‐induced inflammasome activation, inflammatory factors of IL‐1β and TNFα expression.